Analisis Semiotika Makna Pesan Persahabatan Dalam Film Belok Kanan Barcelona (2018) - Kristina, Marya; Cindoswari, Ageng Rara (LPPM Universitas Putera Batam, 2024)
A film is a form of visual art that utilizes moving images and sound to convey a story or message. The film